PUBLIC-GOVERNMENT INTERACTION IN THE DEVELOPMENT OF ARCTIC ANCHOR CITIES: A SOCIOLOGICAL CASE STUDY OF THE MURMANSK REGION - Dmitry L. Kondratovich; Mikhail V. Ulchenko; Roman V. Badylevich (Север и рынок: формирование экономического порядка)
The development of anchor cities in the Russian Arctic as strategically significant urban centers is gaining momentum, underscoring the need to address local challenges. The relevance of this study lies in the growing need to enhance the effectiveness of local governance by fostering more robust interaction between authorities and residents. The article presents the results of a sociological study conducted in the anchor cities of the Murmansk Region. The aim is to evaluate, using sociological survey data, the specific features and forms of interaction between local populations and authorities that shape effective mechanisms for civic engagement and urban governance in the Arctic context. The research is based on data from two surveys conducted by the authors in 2024: an expert survey of scholars participating in the Luzin Readings 2024 academic conference, and a public opinion survey of residents living in the anchor cities of the Murmansk Region. The findings highlight several critical characteristics of public-government interaction in these cities: divergent perceptions of local issues between residents and officials; limited public awareness of governmental activities; the influence of political and economic conditions on civic engagement; the predominantly formal nature of such interactions; and localized factors affecting public interest in social participation. The principal forms of interaction identified include: public participation in decision-making through public hearings; the establishment of advisory councils on matters of urban importance; stakeholder-driven grassroots initiatives (involving authorities, citizens, and civil society organizations); and the provision of consultative support to the population. The study’s scientific novelty lies in its empirical contribution to the theoretical understanding of public-government interaction, achieved through the application of sociological methods. These findings strengthen the evidence base for more informed, effective decision-making in the socio-economic development of Arctic anchor cities. The practical significance of the research lies in its potential to improve the quality of local governance by fostering greater citizen involvement in shaping the future of these strategically important urban areas.